2020
DOI: 10.1093/ajhp/zxz314
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of postinpatient psychiatric follow-up for veterans using telehealth

Abstract: Purpose To describe the implementation and initial outcomes of a pilot interdisciplinary telehealth clinic, Allied Transitional Telehealth Encounters post-iNpatient Discharge (ATTEND), providing clinical pharmacy specialist follow-up for veterans transitioning from inpatient to outpatient mental healthcare in a Department of Veterans Affairs (DVA) hospital. Summary The ATTEND clinic’s primary intervention was providing medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…Rehospitalization rates and time to first MH postdischarge appointment were improved. While Brearly et al 7 provided weekly interventions until the patient established care with outpatient mental health services, the practice described here demonstrates that a pharmacist-led TOC service providing a brief, one-time intervention focused on medication adherence may also improve psychiatric postdischarge outcomes. The limited time and provider resources required for the one-time intervention makes this practice feasible to replicate.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Rehospitalization rates and time to first MH postdischarge appointment were improved. While Brearly et al 7 provided weekly interventions until the patient established care with outpatient mental health services, the practice described here demonstrates that a pharmacist-led TOC service providing a brief, one-time intervention focused on medication adherence may also improve psychiatric postdischarge outcomes. The limited time and provider resources required for the one-time intervention makes this practice feasible to replicate.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, it is among the first to combine the two modalities within the mental health population. Brearly et al 7 described implementation of a pilot telehealth clinic in which a psychiatric pharmacist provided medication management services following psychiatric hospitalization as part of a multidisciplinary team including a clinical psychologist, registered nurse, and psychology technician. Rehospitalization rates and time to first MH postdischarge appointment were improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that video telehealth can offer effective delivery of mental healthcare, [3][4][5] primary care, 6,7 and specialty ambulatory care. 8 -10 Patient populations who face sociodemographic and clinical challenges (e.g., travel distance to care for rural patients) can benefit from video telehealth.…”
mentioning
confidence: 99%
“…These technologies (also referred to as “mHealth”) involve synchronous or asynchronous communications with a clinician and/or interactions (often algorithm‐driven) that include text, video, and interactive/gamified information that trains and reinforces adaptive psychological functioning 35 . Examples beyond videoconference include virtual reality‐based exposure, ecological momentary assessment (symptom monitoring through smartphone‐based data collection), computer/smartphone‐facilitated coping‐skill training/support (VA Web interventions; Breathe2Relax), and text‐based chat with either a computer or a clinician 41 . These approaches, which address treatment barriers including availability, accessibility, and affordability of services, 42 have demonstrated clinical efficacy 43‐45 and provide options for easily accessible, evidence‐based interventions that can supplement in‐person visits or provide options for those who would otherwise not be able to access medical or psychological care.…”
mentioning
confidence: 99%